Manure substitution improves maize yield by promoting soil fertility and mediating the microbial community in lime concretion black soil - Minghui Cao; Yan Duan; Minghao Li; Caiguo Tang; Wenjie Kan; Jiangye Li; Huilan Zhang; Wenling Zhong; Lifang Wu (Journal of Integrative Agriculture, 2024)
Synthetic nitrogen (N) fertilizer has made a great contribution to the improvement of soil fertility and productivity, but excessive application of synthetic N fertilizer may cause agroecosystem risks, such as soil acidification, groundwater contamination and biodiversity reduction. Meanwhile, organic substitution has received increasing attention for its ecologically and environmentally friendly and productivity benefits. However, the linkages between manure substitution, crop yield and the underlying microbial mechanisms remain uncertain. To bridge this gap, a three-year field experiment was conducted with five fertilization regimes: i) Control, non-fertilization; CF, conventional synthetic fertilizer application; CF1/2M1/2, 1/2 N input via synthetic fertilizer and 1/2 N input via manure; CF1/4M3/4, 1/4 N input synthetic fertilizer and 3/4 N input via manure; M, manure application. All fertilization treatments were designed to have equal N input. Our results showed that all manure substituted treatments achieved high soil fertility indexes (SFI) and productivities by increasing the soil organic carbon (SOC), total N (TN) and available phosphorus (AP) concentrations, and by altering the bacterial community diversity and composition compared with CF. SOC, AP, and the soil C:N ratio were mainly responsible for microbial community variations. The co-occurrence network revealed that SOC and AP had strong positive associations with Rhodospirillales and Burkholderiales, while TN and C:N ratio had positive and negative associations with Micromonosporaceae, respectively. These specific taxa are implicated in soil macroelement turnover. Random Forest analysis predicted that both biotic (bacterial composition and Micromonosporaceae) and abiotic (AP, SOC, SFI, and TN) factors had significant effects on crop yield. The present work strengthens our understanding of the effects of manure substitution on crop yield and provides theoretical support for optimizing fertilization strategies.